MDM2 promoter polymorphism del1518 (rs3730485) and its impact on endometrial and ovarian cancer risk. Issue 1 (December 2017) - Gansmo, Liv; Bjørnslett, Merete; Halle, Mari; Salvesen, Helga; Romundstad, Pål; Hveem, Kristian; Vatten, Lars; Dørum, Anne; Lønning, Per; Knappskog, Stian
Abstract Background The del1518 (rs3730485) polymorphism is an in/del variant in theMDM2 promoter P1. The variant is in complete linkage disequilibrium withMDM2 SNP309 (rs2279744) and has previously been found associated with an increased risk of colon cancer. In this study we assessed the impact ofMDM2 del1518 on risk of ovarian and endometrial cancer. Methods Here, we genotyped del1518 in two large hospital-based series of patients diagnosed with ovarian (n  = 1, 385) or endometrial (n  = 1, 404) cancer and performed risk estimations as compared to the genotype distribution among 1, 872 healthy female controls. Results In overall analysis we observed no association between del1518 and risk of either ovarian or endometrial cancer. However, stratifying according to SNP309 status, we found the del1518 variant to be associated with a reduced risk of endometrial cancer among individuals carrying the SNP309TT genotype both in the dominant (OR = 0.64; 95% CI = 0.45 – 0.90) and the recessive model (OR = 0.80; 95% CI = 0.65 – 1.00). No such association was observed for ovarian cancer risk. Conclusion We found theMDM2 del1518 del variant to be associated with reduced risk of endometrial cancer among individuals carrying theMDM2 SNP309TT genotype.